High-Level Programmer's Guide to the 68000 - Mccabe Francis (Prentice Hall, 1992)
An introduction to assembler programming, in particular for the 68000 series of processors including the more advanced 68020 and 68030 models. Aims and Objectives, Introduction, Bits and Bytes and Numbers, The 680x0 Programmer's Model, Representing Pascal Expressions, Pascal Compound Structures, Advanced Pascal Data Structures, Representing Pascal Control, The Pascal Procedure, Symbolic Programming Languages, Prolog, Addressing Modes for the 680x0, The 680x0 Instructions Used in the Text, Answers to Selected Exercises, Index.